Hedonic adaptation to living standards and the hidden cost of parental income - Stefan Boes; Kevin Staub; Rainer Winkelmann (University of Zurich, Socioeconomic Institute, 2007)
High parental income, while undeniably causing benefits for a child in terms of better access to education and more favorable labor market outcomes, may at the same time increase a child's income aspirations and thereby reduce financial satisfaction, ceteris paribus. In this paper, we investigate the relationship between þnancial satisfaction and parental income with data from the German Socio-Economic Panel. The results indicate that there is indeed a negative well-being externality of parental income, and that children appear to compare their actual income situation with the aspiration level acquired while growing up.
Keywords: D62; I31; 330; welfare; happiness; income norm; subjective well-being; Haushaltseinkommen; Eltern; Lebensqualität; Kinder; Deutschland